H7N9: can H7N3 live-attenuated influenza vaccine be used at the early stage of the pandemic?. (January 2014) - Rudenko, Larisa; Isakova-Sivak, Irina; Rekstin, Andrey
<x xml:space="preserve">Abstract</x> As of October 2013, H7N9 avian influenza viruses caused 137 human cases with 45 fatalities. Recent studies revealed that only minor adaptive changes are required for H7N9 viruses to become pandemic. Vaccination is a primary measure to protect population from severe disease and reduce the impact of epidemics and pandemics on public health. Several H7N9 candidate vaccine viruses have been generated and are now undergoing preclinical and clinical testings, which will take several months. Meanwhile, there are several vaccine candidates with H7 hemagglutinin, which can be used to prime the immune system for a robust immune response to booster vaccination with H7N9 vaccine, with perspectives of a substantial dose sparing. H7N3 live-attenuated influenza vaccine besides being attractive priming vaccine in prime–boost strategies, has a potential to protect against H7N9 virus, as was demonstrated by immune epitope analysis and by the detection of cross-reactive antibodies in serum samples of volunteers.